Doing triangulation and mixed methods - Flick, Uwe (SAGE Publications, Inc., 2018)
This book shows you not just how to use triangulation as a strategy of quality management, but also how to use it as an approach to designing and doing qualitative research in a more comprehensive way. Flick links triangulation with current debates about using mixed methods, and outlines their potential for extending qualitative research, addressing questions such as how such research can benefit from integrating quantitative (mixed methods), or from working more generally with more than one approach (triangulation).